Lingual Muscle Activity Across Sleep–Wake States in Rats with Surgically Altered Upper Airway - Rukhadze, Irma; Kalter, Julie; Stettner, Georg M.; Kubin, Leszek (Frontiers in Neurology, 2014)
Obstructive sleep apnea (OSA) patients have increased upper airway muscle activity, including such lingual muscles as the genioglossus (GG), geniohyoid (GH) and hyoglossus (HG). This adaptation partially protects their upper airway against obstructions. Rodents are used to study the central neural control of sleep and breathing but they do not naturally exhibit OSA. We investigated whether, in chronically instrumented, behaving rats, disconnecting the GH and HG muscles from the hyoid (H) apparatus would result in a compensatory increase of other upper airway muscle activity (EMG) and/or other signs of upper airway instability. We first determined that, in intact rats, lingual (GG and intrinsic) muscles maintained stable activity levels when quantified based on 2 h-long recordings conducted on days 6 through 22 after instrumentation. We then studied 5 rats in which the tendons connecting the GH and HG muscles to the H apparatus were experimentally severed. When quantified across all recording days, lingual EMG during SWS was modestly but significantly increased in rats with surgically altered upper airway (8.6% ±0.7(SE) vs. 6.2% ±0.7 of the mean during wakefulness; p=0.012). Respiratory modulation of lingual EMG occurred mainly during SWS and was similarly infrequent in both groups, and the incidence of sighs and central apneas also was similar. Thus, a weakened action of selected lingual muscles did not produce sleep-disordered breathing but resulted in a relatively elevated activity in other lingual muscles during SWS. These results encourage more extensive surgical manipulations with the aim to obtain a rodent model with collapsible upper airway.